NICU Parents of Black Preterm Infants: Application of the Kenner Transition Model. (19th December 2022) - Waldron, Mia K.
Abstract : Background: Black infants in the United States have the highest incidence of both infant mortality (IM) and preterm birth among all racial/ethnic groups. The IM disparity for Black preterm infants often occurs after neonatal intensive care unit (NICU) discharge, when parents become the primary caregivers. The revised Kenner Transition Model (KTM) is situation specific and comprised 5 interrelated domains of parental need after NICU discharge that have not been previously applied to the transition from NICU to home of Black infants. Purpose: This study's purpose was to explore the conceptual fit of parental readiness to care for their Black preterm infants after NICU discharge with the revised KTM. Methods: A qualitative descriptive research approach was used for this single-site study of NICU parents of Black preterm infants. Qualitative analysis of 10 parents' perceptions before NICU discharge was via semantic content analysis; data were organized into categories aligned with the KTM. The Transition Questionnaire (TQ), an adjunct to the KTM, provided self- report quantitative data. Results: All parents endorsed the "Information Needs, " "Stress and Coping, " and "Professional Support" domains of the KTM. Parent TQ responses indicated perceptions of moderate to high levels of home transition readiness after NICU discharge. Implications for Practice and Research: The domains of the revised KTM were affirmed by parents of Black preterm infants in this study via coded interview and TQ responses. Additional study exploring the clinical assessment of transition readiness with theoretical grounding in diverse NICU families is warranted. Video Abstract available at: https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx .